Therapeutic evaluation of electrochemical therapy combined with local injection of pingyangmycin for the treatment of venous malformations in the tongue - Yuan, Weili; Wang, Xukai (Frontiers in Neurology, 2024)
Background Venous malformations are congenital developmental abnormalities that consist of enlarged dysplastic blood vessels. The tongue is a common site of venous malformations in the head and neck region. The aim of the present study was to evaluate the therapeutic effect of using electrochemical therapy (ECT) combined with local injection of pingyangmycin (PYM) for venous malformations in the tongue. Methods 60 patients (20 male and 40 female; age range, 8 to 68 yr) with venous malformations in the tongue were treated with a combination of ECT and PYM injection or with local injection of PYM alone in the department of oral and maxillofacial surgery of the stomatological hospital of China Medical University from January 2013 through June 2019. Among them, 30 patients (group A) were treated with ECT combined with PYM injection for tongue venous malformations and 30 patients (group B) were treated with local injection of PYM alone for tongue venous malformations. The size of the lesions in the two groups varied from 3.5 × 3 × 3 to 8 × 6 × 5 cm. There was no statistical difference in the volume of the lesions between group A and group B (p > 0.05). There was no statistical difference in the age between the two groups (p > 0.05). A repeated treatment of ECT combined with PYM injection or PYM injection alone was administered for venous malformations of tongue in the group A and group B. According to the size of the lesions, the amount of ECT was 5–10 C/cm2. The injection dose of PYM was 3 ~ 5 mL and the injection concentration of PYM was 1.6 mg/mL for adults and 1.0 mg/mL for children. Glucocorticoids were given to prevent postoperative swelling. The therapeutic interval was 3 months for ECT combined with PYM injection and 2 to 4 weeks for PYM injection alone. Hemisphere measurements were used to measure the size of the lesions. 4-scale score and feedback from the patients were used to evaluate the clinical efficacy. Results During the follow-up period from 6 months to 3 years, 60 patients achieved different degree of improvement, with a total effective rate of 85%. 30 patients in the group A received ECT combined with local injection of PYM, with an effective rate of 97%. 30 patients in the group B received local injection of PYM alone, with an effective rate of 73%. The effectiveness of ECT combined with PYM injection in the group A was significantly higher than that of PYM injection alone in the group B (p < 0.05). Postoperative symptoms such as local pain, swelling and fever often occurred in the patients, and the symptoms generally disappeared after 5 to 7 days. No mucosa necrosis or nerve damage was found. Postoperative subjective sensation and function of the tongue were normal. Conclusion Electrochemical therapy combined with local injection of pingyangmycin was a reliable, safe and minimally invasive method for the treatment of venous malformation in the tongue. The treatment modality has fewer complications and is worth of further promotion in clinic.